The Distinction in Student Perceptions' of Female Smokers - Pravitriani, Elsa Novi; Martono, Nanang; Puspitasari, Elis (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study explains the differences in student perceptions of female smokers. The students who were respondents in this study were 2018 students at the University of Palangkaraya and IAIN Palangkaraya. This research was conducted using a survey method with a simple random sampling technique. The number of samples taken was as many as 192. Methods of data analysis using a cross table and Chi Square. There are two research results obtained first, there is no difference in perceptions of female smokers between Palangkaraya University students and IAIN Palangkaraya students. The chi square value is 1.34 and the significance value is 0.24, indicating the relationship between the variables is not significant. Second, there is no difference in perceptions of female smokers between male and female students. The chi squared value of 0.44 and a significance value of 0.50 indicate that the relationship between variables is not significant. Based on the place of study and gender, there is basically no difference in perception. Women who smoke have a negative perspective compared to men who smoke. This is because there is a culture that has been attached to the idea that smoking for women is a very despicable and inappropriate thing.